A Collaborative Process Model for Promoting Successful Referrals in College Counseling. Issue 3 (October 2016) - Iarussi, Melanie M.; Shaw, Brian M.
Abstract : The need to refer students to off‐campus mental health providers is common in college counseling. Such referrals can be challenging for college counselors who strive to meet students' counseling needs while adhering to ethical and center policy guidelines. In this article, the authors explore the nature and challenges of referral in college counseling settings and introduce a collaborative process model to enhance the likelihood of successful referrals. A case study is provided to illustrate the model.